Removal of Cr (VI) by a halotolerant bacterium Halomonas sp. CSB 5 isolated from sÄmbhar salt lake Rajastha (India) - Chandra, P.; Singh, D. P. (Cellular and Molecular Biology, 2014)
A halotolerant chromate reducing bacterium CSB 5 isolated from the Sambhar Salt Lake (Rajasthan) was identified as Halomonas sp. CSB 5 by 16SrDNA sequence analysis. The isolate could tolerate up to 25% NaCl (w/v) and100 µg mL-1of Chromium hexavalent in the complex medium (CM). Removal of Cr (VI) at concentration of 20, 40 and 60 µg mL-1 was found to be 98%, 90.2%, and 65.7% within a period of 60 hour.Effect of factors like pH and temperature on the total removal of Cr (VI) at 60µg mL-1concentration showed maximum removal at pH 8.0 (77.9 %) and temperature 35°C (82.6%) in 60 hour. The maximum intracellular uptake and surface adsorption (3.22 ± 0.09 and 14.16 ± 0.49 µg mg-1 dry wt.) in CMB 5 bacterium was observed at 75 µg mL-1 of Cr (VI) concentration in 45 min.The results showed that contribution of surface binding was about 4-5 fold higher than the intracellular uptake. Bacterium showed concentration dependent increase in the chromate reductase activity with saturating rate at 60 µg mL-1 concentration of chromium. The values of Km and Vmax with NADH of the bacterium was found to be 0.818 µg mL-1 and 0.085 µg mL-1.min-1.mg-1 protein, respectively. Fourier Transform Infrared Spectroscopy (FTIR) analysis of Cr (VI) binding on membrane surface showed changes in wavenumber between 3300-2800 cm-1due to involvement of proteins and fatty acids in the binding of Cr (VI). The absorption peaks at wavenumbers 1654.9, 1580.3 cm-1, 1248 and 1085.6 cm-1 shifted to lower frequencies due to interaction of Cr (VI) with functional groups like amides and phosphodiester. These results suggested that the isolated CSB 5 bacterium can be used as potential bioremediating agent for removal of Cr (VI) in salt loaded waste water.